Influence of graphene oxide on rheology, mechanical, dielectric, and triboelectric properties of poly(vinyl alcohol) nanocomposite hydrogels prepared via a facile one step process. Issue 16 (4th April 2023) - Sharma, Swati; Adaval, Akanksha; Singh, Shiva; Maji, Pradip K.; Subash, Cherumannil Karumuthil; Shafeeq, Valiyaveetil Haneefa; Bhattacharyya, Arup R.
Abstract : The present investigation aims to develop hydrogels with higher mechanical stability for triboelectric applications by adopting a simple method to fabricate a graphene oxide (GO) incorporated poly(vinyl alcohol) (PVA) nanocomposite hydrogel. Abstract : The present investigation aims to develop hydrogels with higher mechanical stability for triboelectric applications by adopting a simple method to fabricate a graphene oxide (GO) incorporated poly(vinyl alcohol) (PVA) nanocomposite hydrogel. Instead of the traditional repeated freeze–thaw method, high-shear solution mixing followed by solvent exchange with deionized water was adopted. Morphological observations showed dense and undulated microstructures in the nanocomposite hydrogel with increased GO concentration. Attenuated Total Reflection Fourier Transform Infrared spectroscopy confirmed a higher degree of intermolecular H-bonding between the hydroxyl group of PVA and oxygenated groups of GO, which leads to a robust gel formation. The formation of a robust PVA/GO nanocomposite hydrogel was examined through rheological investigations at room temperature. Nanoindentation analysis estimated a significant increase in hardness and Young's modulus of the nanocomposite hydrogels. Broadband dielectric spectroscopy showed the variation of the dielectric properties of the PVA/GO nanocomposite hydrogels with increased GO concentration. The PVA/GO nanocomposite hydrogels exhibited a maximum output voltage of 3.65 V at 0.075 wt% GO content during finger tapping experiment suggesting the potential for triboelectric applications. The extensive analysis demonstrates the influence of a very low concentration of GO on the variation of the morphology, rheology, mechanical, dielectric, and triboelectric properties of PVA/GO nanocomposite hydrogels.